Understanding Perinatal Obsessive-Compulsive Disorder (OCD): From prevention to clinical practice - Mulcahy, Melissa Anne (Curtin University, 2021)
This thesis investigated the role of metacognitive beliefs in perinatal obsessive-compulsive disorder (or OCD), including in explaining the onset of OCD in new mothers. It evaluated a novel primary prevention intervention for reducing metacognitive beliefs associated with the onset of OCD symptoms in the postpartum period. Health practitioners’ ability to recognise and respond effectively to perinatal OCD symptoms were also explored, and the thesis made recommendations for clinical education and supervision in perinatal OCD.